Payroll Accounting Information System for Bulumata Lashira Production Employees in Purbalingga - Febriyanti, Susmia; Arnita, Vina (Accounting and Business Journal, 2023)
This research was conducted at the home industry for the manufacture of false eyelash products which is located at Jalan Karang Brai RT 4 RW 2, Mrebet District, Purbalingga Regency, Central Java. The purpose of this study is to determine the payroll accounting information system that is currently running for employees used by business owners. The problems that will be discussed in this study are the calculation of working hours, deductions from salaries/bonuses, low salary payments which will affect employee performance, so that the home industry for Lashira eyelash production has experienced a decrease in both quality and quantity. Methods of data collection carried out in this study using interviews and observation. The data analysis technique used was a qualitative descriptive analysis. The results showed that the implementation of the payroll accounting information system was still not effective, because there were still many factors, namely the absence of a general journal, attendance that was still manual and inaccurate, for example not using fingerprints, payroll and wages and deductions not authorized by the personnel department. The payroll accounting information system will facilitate the systematic calculation of salaries in accordance with good standards. Accounting information systems are very influential to employees and companies because they still use manual methods so they are less effective and can cause errors.